Cascade reaction for the construction of CF3 containing tetrasubstituted furan ring. Issue 106 (1st November 2016) - Choudhary, Manoj K.; Rao Ganga, Venkata Subba; Menapara, Tusharkumar; Kureshy, Rukhsana I.; Khan, Noor-ul H.; Abdi, Sayed H. R.; Suresh, Eringathodi
Abstract : Activated olefins are well known nucleophiles, but proton abstraction from the substituted α-methyl group in nitroolefin is rare. Abstract : Activated olefins are well known nucleophiles, but proton abstraction from the substituted α-methyl group in nitroolefin is rare. We report the first DBU-catalysed one-pot reaction of TFMK and activated nitroolefin followed by intramolecular cyclization reaction, to construct stereogenic center containing a furan core with CF3 in excellent yields (up to >95%).